Comparative study of fuzzy logic speed controller in vector controlled PMSM drive: minimum number of fuzzy rule-base - Siti Noormiza , Mat Isa; Zulkiflie, Ibrahim; Fazlli, Patkar (2009)
This paper presents a comparative study on fuzzy rule-base of fuzzy logic speed control with vector-controlled Permanent Magnet Synchronous Motor (PMSM) drive. Fuzzy rule-base design is viewed as control strategy. All fuzzy rules contribute to some degree in obtaining the desired performance. However, some rules tired weakly do not contribute significantly to the final result and can be eliminated. 'Standard design' of fuzzy rule-base of fuzzy logic controller is identified from numerous publications which is 49 rules is used in order to obtain great speed tracking response. It is possible to minimize the complexity of controller's design by reducing number of rule-base from standard 49 rules to 9 rules. Simulation results that verify appropriateness of the approach are included. A comparison of speed response between both designs is studied. Sensitivity of the designs to load disturbance and changes in command settings is studied and also being compared to demonstrate the effectiveness of the reduced rule base.